Consumers’ Perception of Item-Level RFID Use in FMCG: A Balanced Perspective of Benefits and Risks - Kukard, Wesley Andrew (Auckland University of Technology, 2015)
The main purpose of this thesis is to explore how perceived consumer benefits affect the perceived privacy risks associated with the implementation of Radio Frequency Identification (RFID) tags at an item-level within the Fast Moving Consumer Goods (FMCG) industry. This research expanded upon Smith et al. (2013) that explored the idea of consumer benefits for RFID at an item-level, which only considered benefits within a store environment. This thesis proposes two new categories to measure benefits and risks, in-store and after sale. By splitting these benefit and risk categories, the respondents’ willingness to accept RFID in both a public (grocery store) and private (home) environment could be measure individually. To test the theory a quantitative survey was conducted using primary household purchasers within the USA. A total of 261 responses were received and were subjected to a PLS-SEM data analysis through SmartPLS software. The results suggest that while consumers’ seem to be aware that there could be a certain degree of risk while using RFID both in-store and after sale, they would still be willing to use the technology if there were sufficient benefits. This research has both practical and theoretical contributions, as a study into how the benefits of RFID could affect consumer acceptance of RFID, It creates a framework for future researchers to explore the topic in more in-depth studies. However, the study was limited to grocery purchasers within the United States of America (USA) between the ages of 18 and 65. While the study focused on perceived benefits and risks for the grocery purchaser, it does not take into account the rest of the household’s perception of potential benefits and risks for this technology. In practical terms, this research gives practitioners reason to consider consumer benefits as a strategy for item-level RFID implementation within the FMCG industry and importantly starts to build a case for a bottom-up approach to the implantation of RFID as apposed to the enormous cost of an entire supply chain fit out. This research changes the conversation within RFID literature, moving away from a focus on consumer privacy issues to a balanced privacy / benefits approach for consumers and how that might affect their technology acceptance.
Keywords: Item-level RFID; Consumer acceptance; FMCG; Technology acceptance; Consumer benefits; Consumer risks